Meta-analysis evaluating the impact of chili-pepper intake on all-cause and cardiovascular mortality: A systematic review. (October 2021) - Yamani, Naser; Musheer, Adeena; Gosain, Priyanka; Sarfraz, Saba; Qamar, Humera; Waseem, Muhammad Maaz; Arshad, Muhammad Sameer; Almas, Talal; Figueredo, Vincent
Abstract: Background: Dietetics today occupy a significant place in the field of research, helping to discover cardiovascular benefits of healthy diets and consumption of organic foods such as fruits, vegetables, legumes, nuts, and whole grains. One of the components of vegetable-based diet is chili pepper (CP) which has been found to affect all-cause mortality. Methods: MEDLINE, EMBASE, Scopus, EBSCO, and Cochrane (Wiley) Central Register of Controlled Trials were searched from inception till January 9, 2020, identifying all relevant studies using keywords and truncations. Studies were included if (1) they were observational or randomized in nature (2) included patients consuming CP and (3) evaluated direct comparison between regular and rarely/never CP consumption. Results: Our preliminary search yielded 6976 articles. Post exclusion and after full-text screening, four potential observational studies with a population of 570, 762. Pooled analysis found reduced all-cause mortality in CP consumers compared to nonconsumers with a risk ratio (RR) of 0.75 [95% CI: 0.64–0.88; p = 0.0004; I 2 = 97%]. The RR for CVD, cancer related and CVA deaths were 0.74 [95% CI: 0.62–0.88; p = 0.0006, I 2 = 66%], 0.77 [95% CI: 0.71–0.84; p = 0.0001; I 2 = 49%] and 0.76 [95% CI: 0.36–1.60; p = 0.47; I2 = 93%], respectively. Conclusion: Statistically significant results of our analysis put forward a rationale indicating an association between lower risk of all-cause, cardiovascular and cancer related deaths and CP consumption. Highlights: Cardiovascular diseases have been observed to be a major cause of mortality. Recent transition to vegetable-based diet including Chili Pepper is positively impacting health of cardiovascular patients. Capsaicin affects TRPV1 Receptors and consequently weight-reduction.